(untitled) (Nigerian Journal of Physiological Sciences, 2021)
Summary: The study investigated the role of adrenergic receptors in glucose, fructose-, and galactose- induced increases in intestinal glucose uptake. Experiments were carried out on fasted male anaesthetized Nigerian local dogs divided into seven groups (with five dogs per group). Group I dogs were administered normal saline and served as control. Dogs in groups II, III and IV were intravenously infused with glucose (1.1 mg/kg/min), fructose (1.1 mg/kg/min) and galactose (1.1 mg/kg/min) respectively. Another three groups, V, VI and VII were pretreated with prazosin (0.2mg/kg), propranolol (0.5mg/kg) or a combination of prazosin (0.2mg/kg) and propranolol (0.5mg/kg) followed by glucose infusion, frutose infusion or galactose infusion respectively. Through a midline laparatomy, the upper jejunum was cannulated for blood flow measurement and blood samples were obtained for measurement of glucose content of the arterial blood and venous blood from the upper jejunal segment. Glucose uptake was calculated as the product of jejunal blood flow and the difference between arterial and venous glucose levels (A-V glucose). The results showed that pretreatment of the animal with prazosin had no effect on glucose and galactose induced increases in glucose uptake. However, pretreatment with propranolol completely abolished glucose, fructose and galactose-induced increases in intestinal glucose uptake. Prazosin also significantly reduced galactose-induced increase in intestinal glucose uptake. The results suggest that the increases in intestinal glucose uptake induced by glucose and fructose are mediated mostly by beta adrenergic receptors while that of galactose is mediated by both alpha and beta adrenergic receptors.